The C‐terminal portion of the cleaved HT motif is necessary and sufficient to mediate export of proteins from the malaria parasite into its host cell. Issue 4 (21st January 2013) - Tarr, Sarah J.; Cryar, Adam; Thalassinos, Konstantinos; Haldar, Kasturi; Osborne, Andrew R.
Summary The malaria parasite exports proteins across its plasma membrane and a surrounding parasitophorous vacuole membrane, into its host erythrocyte. Most exported proteins contain a Host Targeting motif (HT motif) that targets them for export. In the parasite secretory pathway, the HT motif is cleaved by the protease plasmepsin V, but the role of the newly generated N‐terminal sequence in protein export is unclear. Using a model protein that is cleaved by an exogenous viral protease, we show that the new N‐terminal sequence, normally generated by plasmepsin V cleavage, is sufficient to target a protein for export, and that cleavage by plasmepsin V is not coupled directly to the transfer of a protein to the next component in the export pathway. Mutation of the fourth and fifth positions of the HT motif, as well as amino acids further downstream, block or affect the efficiency of protein export indicating that this region is necessary for efficient export. We also show that the fifth position of the HT motif is important for plasmepsin V cleavage. Our results indicate that plasmepsin V cleavage is required to generate a new N‐terminal sequence that is necessary and sufficient to mediate protein export by the malaria parasite.